Coole Forschung Lernen und Forschen im Internationalen Polarjahr 2007/2008 - Schöner, Wolfgang (alpine space - man and environment, 2012)
BiPolar was a pioneer project of the sparkling Science framework. BiPolar was also a contribution to the international Polar Year 2007/2008. BiPolar is a research-educational cooperation. BiPolar is modular. Each module uses polar research as a starting point. The integration of students leads to a step by step cooperation between science and education to develop research foci suitable for primary and secondary education.